Alternative to efficiency correction using soluble BOD in stabilization ponds (Revista de Diavulgación L'esprit Ingénieux, 2024)
Stabilization ponds are a wastewater treatment system widely used in developing geographical areas. These systems are characterized by their large space requirements in terms of area due to the extended hydraulic retention times needed for organic matter removal from wastewater. One of the most well-known methods was proposed in 1970 by McGarry & Pescod. This model is primarily empirical and based on experiments conducted on physical models. Some uncertainties have arisen over the years since its application as a design model, one of which is the use of soluble Biochemical Oxygen Demand (BOD) as a parameter for primary effluent correction to provide further treatment. This article presents a more intuitive alternative to the correction process using soluble BOD, which involves the maximum organic surface load and the organic load removed from the primary effluent. The application of this premise resulted in theoretical efficiencies exceeding 90% throughout the treatment system
Keywords: Wastewater; wastewater treatment; treatment plants; BOD; soluble BOD; WWTP; Ponds